Production of fresh fish sausages containing natural preservatives (Laurus nobilis L.) it’s nutritional composition and oxidative stability - Çoban, Özlem Emir (Progress in Nutrition, 2020)
Aim: The aim of this study was develop the fresh fish sausage containing natural protective from rainbow trout (Oncorhynchus mykiss) and it’s was investigate the nutritional composition and oxidative stabil- ity during storage at 2˚ C. Method: For this purpose were stored the fresh trout sausages added 2% Laurus nobilis extract and 4% Laurus nobilis extract for 10 days. Three different sausage formulations were analyzed for nutritional composition and lipid oxidation products (total volatile base nitrogen (TVB-N) thiobarbituric acid (TBA), peroxide value (PV ) and free fatty acids (FFAs)). Results: The formulated fresh trout sausages determined 68.11-68.26% moisture, 18.06-18.25% protein, 6.12-6.15% lipid, 3.14-4.28% ash as “good qual- ity” and “ might buy”. According to oxidative stability results the highest levels of TVB-N TBARS, PV and FFAs were related to the control group and the least amount of these parameters was determined in Lauris nobilis extract (LE) applications. Conclusion: Based on the this datas, it can be deduced that the LE success- fully improve the oxidative stability of the fresh trout sausages in the cold storage